KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA (STUDI KASUS DI DESA NAIMANA KECAMATAN MALAKA TENGAH KABUPATEN MALAKA) - Oswaldus Liquori Seran; Rodriques Servatius; Eusabius Separera Niron (Journal Education and Government Wiyata, 2025)
This research is titled "The Leadership of the Village Head in Enhancing Community Participation in Village Development (A Case Study in Naimana Village, Malaka Tengah Subdistrict, Malaka Regency)." The primary objective of this study is to explore the leadership of the Village Head and the community's participation in the development of Naimana Village, Malaka Tengah Subdistrict, Malaka Regency. The research employs a qualitative descriptive method, utilizing interviews, observations, and documentation techniques. The findings reveal that the leadership of the Village Head plays a crucial role in increasing community participation in village development. A proactive Village Head who engages directly with the community and is able to accept and respond to criticism wisely has a significant impact on encouraging public involvement in the development process. First, proactive leadership accelerates communication between the village government and the community, allowing the needs and expectations of the people to be quickly identified in development policies. Second, the Village Head’s ability to accept criticism and suggestions from the community demonstrates that open and democratic leadership fosters a conducive environment for dialogue and collaboration in village development.